Die Bernoulli Ungleichung

Behauptung:

$$(1+x)^n \geq 1+n\cdot x \quad\quad x\geq -1 \quad\quad n\geq 1$$



Beweis:

Induktionsanfang: n = 1

$$(1+x)^1~=~1+x~\geq~1+1\cdot x$$

Induktionsschritt: A(n) => A(n+1)

$$\begin{align*} (1+x)^{n+1} &=~(1+x)^n\cdot (1+x)\\ &\geq~(1+nx)(1+x)\quad\quad [Induktionsvoraussetzung~wurde~eingesetzt]\\ &=~1+x+nx+nx^2\\ &\geq~1+nx+x\quad\quad\quad [x^2~und~damit~nx^2~ist~immer~eine~positive~Zahl]\\ &=~1+(n+1)x\end{align*}$$

q.e.d.

Weiterlesen: Just another Ungleichung